2006
DOI: 10.4049/jimmunol.176.3.1588
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Heat Shock Protein 70-Peptide Complexes Induce NK Cell-Dependent Tolerance to Experimental Autoimmune Encephalomyelitis

Abstract: Heat shock proteins (Hsp) are markedly up-regulated at sites of inflammation during autoimmune diseases like experimental autoimmune encephalomyelitis (EAE). In this study, we show that Hsp70-peptide complexes (pc) isolated from brains of mice with EAE prevented the development of EAE clinically and pathologically when administered before proteolipid protein 139–151 (PLP139–151) immunization. In contrast, pure Hsp70 or Hsp70-pc derived from brains of healthy mice or other inflamed tissue did not modulate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Searching for mechanisms of immune regulation, we have assessed the role of induction of stress-related peptides at sites of inflammation. In our previous study (21), we showed that a peptide fraction, isolated from EAE brain tissue and chaperoned by the stress-induced protein heat shock protein 70 (Hsp70-pc), induced a state of tolerance through the induction of regulatory NK cells. In this study, we investigated the role of H60 and the NKG2D receptor in the Hsp70-pc-induced inhibition of EAE.…”
Section: E Nhancement Of Immunoregulation That Results In Limiting Aumentioning
confidence: 99%
See 3 more Smart Citations
“…Searching for mechanisms of immune regulation, we have assessed the role of induction of stress-related peptides at sites of inflammation. In our previous study (21), we showed that a peptide fraction, isolated from EAE brain tissue and chaperoned by the stress-induced protein heat shock protein 70 (Hsp70-pc), induced a state of tolerance through the induction of regulatory NK cells. In this study, we investigated the role of H60 and the NKG2D receptor in the Hsp70-pc-induced inhibition of EAE.…”
Section: E Nhancement Of Immunoregulation That Results In Limiting Aumentioning
confidence: 99%
“…Hsp70 preparations were isolated and purified according to previously published protocols (21,22). In brief, CNS tissue was homogenized, centrifuged, and loaded on PD10-column.…”
Section: Purification Of Hsp70 Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…48 However, there are also contradicting findings regarding the contribution of HSP to MS onset. 49 Defective expression of HSP has been suggested to contribute to the neurodegenerative phenomena observed in longterm MS. 50 By contrast, it has been shown that HSP70 binds MBP and proteolipid protein (PLP) peptides, generating immunogenic complexes that might be able to trigger autoimmune responses in mouse models of MS. 51 Similarly, molecular mimicry between bacterial and mammalian HSP has been implicated in the pathogenesis of MS. 52 This suggests that upregulation of key antigens; for instance, the HSP70 might increase the susceptibility to CNS autoimmune disease onset. Therefore, it is not meaningless to suggest that HSP, MOG and others might constitute key antigens from the CNS that are early recognized by the immune system during brain structuring.…”
Section: Immunological Homunculus For Cns Antigens: First Hints From mentioning
confidence: 99%